Pengaruh Kebijakan Dividen, Kebijakan Utang dan Managerial Ownership terhadap Nilai Perusahaan - Mareta Hendrayanti Florensia Indah Budiati; Fina Fitriyana (AKUA: Jurnal Akuntansi dan Keuangan, 2024)
This research aims to determine the influence of dividend policy, debt policy and managerial ownership on company value in companies listed on the Indonesian Stock Exchange for the 2018-2022 period. Dividend Policy is measured by using DPR, Debt Policy is measured by using DER, Managerial Ownership is measured by the number of shares owned by the managerial paty (manager and directors) divided by the total outstanding shares. The population in this study is consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The number of samples in this study was 6 with a 5-year obeservation method in the 2018-2022 period and the number of financial statements used as samples in this study amounted to 30. A population of 113 companies was obtained. Based on the purposive sampling method, a sample of 6 companies was obtained. The results of this research show that (1) Dividend policy has an effect on company value, (2) debt policy has an effect on company value, (3) managerial ownership has no effect on company value.